Effect of hot red pepper supplementation and different storage times on hen egg quality - Hanif, Muhammad Fathin; Ariyadi, Bambang; Muhlisin, Muhlisin; Al-Huda, Muhammad Asyraf; Luschandina, Chiyaruna Zulfa; Agus, Ali (Agronomía Mesoamericana, 2024)
Introduction. Eggs are a food source of protein that easily deteriorates during storage. Supplementation of hot red chili pepper powder, rich in bioactive compounds, in diets for laying hens can improve egg quality and prevent egg deterioration during storage. Objective. To determine the effect of hot red pepper powder supplementation and different storage times on the physical egg quality of laying hens. Materials and methods. This study was conducted from January to March 2024 at the Research Barn of PT Agromix Lestari Group, Kulon Progo, Yogyakarta, Indonesia. Eighty 56-week-old Novogen laying hens (1681 ± 64 g) were assigned into four dietary treatments (four replications, five hens per replication): basal diet as control (P0); basal diet + 0.25 % hot red pepper powder (P1); basal diet + 0.5 % hot red pepper powder (P2), and basal diet + 0.75 % hot red pepper powder (P3). At the end of week 6, one egg per replicate group was collected and analyzed for physical quality in three storage treatments: fresh condition (S0), one week storage (S1) and two weeks storage (S2). Egg quality data were analyzed with a factorial experimental design (4 × 3) using SPSS 26 software. Results. Supplementation of 0.5 % hot red pepper powder significantly increased egg weight. Hot red pepper addition and treatment duration significantly affected egg yolk color. The hot red pepper treatment group showed significantly lower pH of albumen and yolk. Conclusions. The supplementation of hot red pepper powder in laying hens’ diets has been shown to improve egg yolk color. The inclusion of 0.5 % in the ration was able to keep the pH of yolk and albumen low.